THE EFFECTIVENESS OF PARTICIPATIVE LEADERSHIP STYLE THEORY ON THE PERFORMANCE OF MADRASAH TSANAWIYAH EDUCATORS AL-HIDAYAH SERANG - Royani, A. Royani; Fauzi, Anis; Zohriyah, Anis (Jurnal Konseling Pendidikan Islam, 2024)
This study aims to appreciate the leadership of the principal of Madrasah Tsanawiyah Al-Hudayah Serang who uses a participatory leadership style. This research will show the results of improved performance in the institution, in the aspect of improving teacher performance. To get the results of the study, researchers use qualitative methods that use interview approaches and social analysis. The results of this study show an increased teacher performance based on the leadership style carried out by the principal of Madrasah Tsanawiyah Al-Hidayah Serang, as evidenced by the increased participatory aspect of a teacher and the planned program is running well. In addition, in this study there is a review of theories that can be a reference for implementing the effectiveness of participatory leadership styles, namely; 1). Participatory leadership dynamics; 2). Decision-making process; 3). Conflict management strategies; 4). Active communication strategy; 5). The existence of the absence of educators.